Pollen Streptomyces Produce Antibiotic That Inhibits the Honey Bee Pathogen Paenibacillus larvae - Grubbs, Kirk J.; May, Daniel S.; Sardina, Joseph A.; Dermenjian, Renee K.; Wyche, Thomas P.; Pinto-Tomás, Adrián A.; Clardy, Jon; Currie, Cameron R. (Frontiers in Microbiology, 2021)
Humans use natural products to treat disease; similarly, some insects use natural products produced by Actinobacteria to combat infectious pathogens. Honey bees, Apis mellifera, are ecologically and economically important for their critical role as plant pollinators and are host to diverse and potentially virulent pathogens that threaten hive health. Here, we provide evidence that Actinobacteria that can suppress pathogenic microbes are associated with Apis mellifera. We show through culture-dependent approaches that Actinobacteria in the genus Streptomyces are commonly isolated from foraging bees, and especially common in pollen stores. One strain, isolated from pollen stores, exhibited pronounced inhibitory activity against Paenibacillus larvae, the causative agent of American foulbrood. Bioassay-guided HPLC fractionation, followed by NMR and mass spectrometry, identified the known macrocyclic polyene lactam, piceamycin that was responsible for this activity. Further, we show that in its purified form, piceamycin has potent inhibitory activity towards P. larvae. Our results suggest that honey bees may use pollen-derived Actinobacteria and their associated small molecules to mediate colony health. Given the importance of honey bees to modern agriculture and their heightened susceptibility to disease, the discovery and development of antibiotic compounds from hives could serve as an important strategy in supporting disease management within apiaries.